RETRACTED: Long Non-coding RNA LINC00320 Inhibits Tumorigenicity of Glioma Cells and Angiogenesis Through Downregulation of NFKB1-Mediated AQP9 - Chang, Lisha; Bian, Zhe; Xiong, Xin; Liu, Jian; Wang, Dali; Zhou, Fuling; Zhang, Jiang; Zhang, Yunhe (Frontiers in Cellular Neuroscience, 2020)
The inhibitory effect of long intergenic non-coding RNA 00320 (LINC00320) in glioma cell proliferation has been proposed in a recent study. However, the mechanisms by which LINC00320 regulate aquaporin 9 (AQP9) in glioma require further exploration. Hence, this study aims to investigate effects of LINC00320 on tumorigenicity of glioma cells and angiogenesis of microvascular endothelial cells (MVECs). Expression of LINC00320 and AQP9 in glioma tissues and cells was measured by reverse transcription–quantitative polymerase chain reaction and Western blot analysis. The relationship among LINC00320, nuclear factor κB subunit 1 (NFKB1) and AQP9 was examined by RNA immunoprecipitation, dual-luciferase reporter gene, and chromatin immunoprecipitation assays. The participation of LINC00320 and AQP9 in glioma cell proliferation and MVEC angiogenesis was analyzed using gain- and loss-of-function approaches. Finally, a nude mouse orthotopic xenograft model of glioma was established to investigate the effects of LINC00320 and AQP9 on glioma growth in vivo. LINC00320 was under-expressed and AQP9 was over-expressed in glioma tissues. Further mechanistic investigation showed that LINC00320 downregulated AQP9 by inhibiting the recruitment of NFKB1 to the promoter region of AQP9. LINC00320 overexpression or AQP9 silencing inhibited the proliferation of glioma cells and angiogenesis of MVECs. Also, upregulation of LINC00320 restrained tumor growth and angiogenesis in xenograft mice by downregulating AQP9. Taken together, LINC00320 acts as a tumor suppressor in glioma, thus presenting a novel therapeutic target.